Culture and cognition patterns in the social construction of reality - Brekhus, Wayne H. (Cultural sociology (Polity Press), 2015)
How does culture shape our thinking? In what ways do our social and cultural worlds enter into our mental worlds? How do the communities we belong to influence what we notice and what we ignore? What cultural variation do we see in cognition? What general patterns do we see across this diversity and variation? In this lively and engaging book, Wayne H. Brekhus shows us the many ways that culture influences our cognitive thought processes. Drawing on a wide range of fascinating examples, such as how members of different subcultures perceive danger and safety, how cultures variably classify and perceptually weight race, how social actors use and present identity as a strategic resource, and how people across different organizational settings experience time, Brekhus takes us on a creative, diverse, and insightful tour of the sociocultural character of cognition. Culture and Cognition: Patterns in the Social Construction of Reality offers an invaluable survey of a wide-ranging body of research in the sociology of culture and cognition that will be an inviting resource for upper-level undergraduates, graduate students, and established research scholars alike.